Skeletal Class II open-bite malocclusion with idiopathic condylar resorption: a case report - Oka Ayaka; Kurosaka Hiroshi; Yashiro Kohtaro; Haraguchi Seiji; Lee Donghoon; Aikawa Tomonao; Kogo Mikihiko; Yamashiro Takashi (Sciendo, 2018)
The orthodontic treatment of patients with idiopathic condylar resorption (ICR) remains controversial. The effect of molar intrusion using temporary anchorage devices (TADs) and the consequential gradual counterclockwise rotation of the mandible in patients with ICR remains unclear.